1993
DOI: 10.1021/es00040a014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biological treatment on halogenated organics in bleached kraft pulp mill effluents studied by molecular weight distribution analysis

Abstract: The removal potential of different biological treatments of organohalogen compounds in kraft pulping and bleaching effluents was studied by nonaqueous size-exclusion chromatography and grouping the compounds by solubility and adsorption characteristics. Organohalogen compounds of waste waters from five pulp mills with different processes exhibited similar molecular weight distributions, ranging from 100 to 4000. The anaerobic/ aerobic lagoon system removed 58-66% of the organochlorine compounds from the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 11 publications
2
17
0
2
Order By: Relevance
“…Results in Table 1 and similar findings reported elsewhere (4), show that the percentage of AOX removal during biopurification of wastewater was around 50%. The removal efficiency was similar, about 50%, for both the carbon and the halogen.…”
Section: Biodegradation and Human Exposure To Chlorobleaching Organicsupporting
confidence: 89%
“…Results in Table 1 and similar findings reported elsewhere (4), show that the percentage of AOX removal during biopurification of wastewater was around 50%. The removal efficiency was similar, about 50%, for both the carbon and the halogen.…”
Section: Biodegradation and Human Exposure To Chlorobleaching Organicsupporting
confidence: 89%
“…As discussed earlier, it is widely reported that the residual recalcitrant organic matter is composed predominantly by high molecular weight components, which are not metabolized due to its size. However, the contributions of high and low molecular weight fractions in bio-treated effluents are dissimilar [36]. In the LMW fraction, a large-scale removal of the chlorinated phenolic compounds, chlorinated resin acids and sterols occurs.…”
Section: Aerobic Treatability Of the Different Effluent Fractionsmentioning
confidence: 99%
“…Although in most cases the toxicity is low, effluents from pulp bleaching are characterized by high strength of COD (1000 to 7000 mg L -1 ), low biodegradability ratio (BOD5/ COD) ranging from 0.02 to 0.07, and a moderate strength of suspended solids (500 to 2000 mg L -1 ) Eskelinen et al 2012). Compounds, especially those containing chlorine (measured by the parameter AOX) are recalcitrant because they contain chemical structures uncommon in nature, such as the carbon-chlorine bond (Jokela et al 1993;Mounteer et al 2007a). It is widely reported that high molecular weight (HMW > 1 kDa) organic matter in bleaching effluents is more recalcitrant to biological treatment than low molecular weight (LMW < 1 kDa) organic matter (Dahlman et al 1995;Savant et al 2006).…”
mentioning
confidence: 99%